Mission impossible? Pursuing the co-existence of viable predator populations and sustainable reindeer husbandry in Finland - Rasmus, Sirpa; Kojola, Ilpo; Turunen, Minna; Norberg, Harri; Kumpula, Jouko; Ollila, Tuomo
2020